The Role of Reactive Oxygen Species in Arsenic Toxicity - Hu, Yuxin; Li, Jin; Lou, Bin; Wu, Ruirui; Wang, Gang; Lu, Chunwei; Wang, Huihui; Pi, Jingbo; Xu, Yuanyuan (Biomolecules (Basel, Switzerland), 2020)
Arsenic poisoning is a global health problem. Chronic exposure to arsenic has been associated with the development of a wide range of diseases and health problems in humans. Arsenic exposure induces the generation of intracellular reactive oxygen species (ROS), which mediate multiple changes to cell behavior by altering signaling pathways and epigenetic modifications, or cause direct oxidative damage to molecules. Antioxidants with the potential to reduce ROS levels have been shown to ameliorate arsenic-induced lesions. However, emerging evidence suggests that constructive activation of antioxidative pathways and decreased ROS levels contribute to chronic arsenic toxicity in some cases. This review details the pathways involved in arsenic-induced redox imbalance, as well as current studies on prophylaxis and treatment strategies using antioxidants.